1997
DOI: 10.1159/000159233
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Effects of Proteinase-Activated Receptor 2 Agonist Peptide

Abstract: Proteinase-activated receptor 2 (PAR-2) is a G protein-coupled receptor related to the thrombin receptor. PAR-2 can be activated by trypsin and by synthetic peptides corresponding to the new amino terminus generated by activating proteolytic cleavage. We show in this report that intravenous injection of PAR-2 agonist peptides has dramatic effects on arterial blood pressure in anesthetized rats. The peptide SLIGRLETQPPI, at 150 nmol/kg, transiently decreased the mean arterial pressure from 104 to 60 mm Hg. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
58
2
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 15 publications
10
58
2
1
Order By: Relevance
“…The present results clearly show that PAR-2 activation causes vasodilation in healthy humans in vivo, and in this respect, the results are similar to those seen in experimental animals. 12,13 Interestingly, in studies of isolated human vessels, pretreatment with either interleukin-1 (IL-1) or tumor necrosis factor-␣ (TNF-␣) upregulated PAR-2 expression and, in the coronary artery, revealed endothelium-dependent vasodilatation to PAR-2-activating peptides. 14 This response was abolished by either removal of the endothelium or combined treatment with N-nitro-L-arginine (an NO synthase [NOS] inhibitor) and indomethacin.…”
Section: Discussionmentioning
confidence: 99%
“…The present results clearly show that PAR-2 activation causes vasodilation in healthy humans in vivo, and in this respect, the results are similar to those seen in experimental animals. 12,13 Interestingly, in studies of isolated human vessels, pretreatment with either interleukin-1 (IL-1) or tumor necrosis factor-␣ (TNF-␣) upregulated PAR-2 expression and, in the coronary artery, revealed endothelium-dependent vasodilatation to PAR-2-activating peptides. 14 This response was abolished by either removal of the endothelium or combined treatment with N-nitro-L-arginine (an NO synthase [NOS] inhibitor) and indomethacin.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of PAR-2-elicited inflammation consist of multiple cascades, including increase of vascular permeability, cytokine production, and expression of adhesion molecules that further lead to leukocyte accumulation (19). Additionally, PAR-2-stilumated secretion of prostanoids (33) and NO (34) may enhance the inflammatory responses, while activation of PAR-2 in nerve endings induces the release of calcitonin gene-related peptide (CGRP) and substance P (35). Therefore, the future development of PAR-2 antagonists can be therapeutically beneficial for treatment of a number of inflammatory diseases such as allergic dermatitis, rheumatoid arthritis, asthma, inflammatory bowel disease, and neurogenic pain.…”
Section: Par-2 As a Therapeutic Targetmentioning
confidence: 99%
“…PAR-2 may also contribute to regulation of vascular tone, since PAR-2 mRNA is present in highly vascularized tissues 5 and application of trypsin or the PAR-2 agonist peptide produces endothelium-dependent relaxation of peripheral arteries in vitro. [6][7][8][9] Furthermore, in anesthetized rats hypotension is produced when the agonist peptide corresponding to the tethered ligand sequence in the mouse and the rat (SLIGRL) is injected intravenously, 8,9 possibly indicating that PAR-2-mediated vasodilatation also occurs in vivo.…”
Section: See Editorial Comment Page 1444mentioning
confidence: 99%
“…Previous indirect studies have indicated that PAR-2 activation may produce vasodilatation in vivo. The hypotensive effect of intravenous injection of SLIGRL was reported to be accompanied by baroreflex-mediated tachycardia and sympathetic nerve activation, 8,9 suggesting that the decrease in arterial pressure was associated with a decrease in total peripheral resistance rather than in cardiac output. The present findings, in which topical application of PAR-2 activators produced increases in basilar artery diameter in the absence of any change in systemic arterial blood pressure, confirm directly that PAR-2-mediated vasodilatation occurs in vivo in the cerebral circulation.…”
Section: Functional Importance Of Par-2mentioning
confidence: 99%